The Inculcation of the Students’s Spiritual Values to Shape Students’ Character in SMP Negeri 1 Bantul Yogyakarta - Nashatun Nashatun; Irfat Salam (INNOVATIO: Journal for Religious Innovation Studies, 2020)
Inculcating the spiritual values ​​is fundamental in shaping human personality so that they are able to behave based on Islamic principles. Thus, this study aims to describe the inculcation of values ​​to students in SMP Negeri 1 Bantul Yogyakarta. This research is a qualitative research, with a descriptive type of field research, which intends to describe how to instill spiritual values ​​in students. The research subjects were teachers at SMP Negeri 1 Bantul Yogyakarta. Data collection techniques were carried out by observation, interviews, and documentation, while the data analysis used is the Miles and Huberman model analysis; data reduction, data presentation, and data verification. The results showed that the spiritual values ​​instilled in students were very diverse, ranging from religious values, aesthetic values, moral values, and truth values. The cultivation of these spiritual values ​​is given through the learning process or through various activities and programs at SMP Negeri 1 Bantul Yogyakarta, such as the tahfidz al-Qur'an program, halaqah tarbawiyah, dhuha prayer in congregation, dzuhur prayer in congregation , and Friday prayers in congregation. Abstrak: Penanaman nilai spiritual adalah hal mendasar dalam membentuk kepribadian manusia agar mampu berprilaku Islami. Sehingga, penelitian ini bertujuan untuk menguraikan penanaman nilai terhadap perserta didik di SMP Negeri 1 Bantul Yogyakarta. Penelitian ini merupakan penelitian kualitatif, dengan jenis penelitian lapangan yang bersifat deskriptif yaitu penelitian yang bermaksud menggambarkan bagaimana penanaman nilai-nilai spiritual terhadap peserta didik. Subjek penelitiannya adalah guru di SMP Negeri 1 Bantul Yogyakarta Teknik pengumpulan data dengan observasi, wawancara, dan dokumentasi, sedangkan analisis datanya menggunakan analisis model Miles dan Huberman yaitu: reduksi data, penyajian data, dan verifikasi data. Hasil penelitian menunjukkan bahwa nilai-nilai spiritual yang ditanamkan kepada peserta didik sangatlah beragam mulai dari nilai religius, nilai estetika, nilai moral, dan nilai kebenaran. Penanaman nilai-nilai spiritual tersebut diberikan melalui proses pembelajaran ataupun melalui berbagai macam kegiatan dan program yang ada di SMP Negeri 1 Bantul Yogyakarta, misalnya seperti program tahfidz al-Qur’an, halaqah tarbawiyah, shalat dhuha berjama’ah, shalat dzuhur berjama’ah, dan shalat jum’at berjama’ah.